A Hay Rake-Making Business at West Mill, Askrigg, Wensleydale, North Yorkshire. (1st January 2017) - Richardson, Shaun
Abstract: Between the late-nineteenth and mid-twentieth centuries, West Mill, in Askrigg, North Yorkshire, was the base of a regionally important hay rake making business undertaken by the Burton family. Set within Wensleydale, an agricultural landscape organised around hay making, hay rakes made by the Burtons were sold across much of the north of England. Using documentary, archaeological, and oral evidence, this paper examines the construction of a typical Burton hay rake, the surviving evidence for this process at West Mill, and how the rakes were used. The significance of the business to the wider Wensleydale agricultural community is also discussed.